Design of diamond drill heads with a hydrojet effect of rock destruction - Mendebaev, Toktamys; Smashov, Nurlan (Eastern-European Journal of Enterprise Technologies, 2022)
It follows from the analysis of materials related to the design and operation of drilling equipment that an important direction in the search for effective solutions appears to be the improvement of the structure of the working matrix of diamond drilling heads and the enhancement of their technological capabilities by using in their schemes physical effects that are unconventional in the field of well drilling technology. The tasks to be solved are to reduce the energy costs of the process of deepening wells, to obtain a structurally integral, informative core, and to ensure the stability of well walls. Following the concept, diamond drill heads with a separate system of washing channels and a hydrojet effect of rock destruction were designed and tested during the drilling of wells. The novelty of the structure of drill heads is the direction of the pressure flow of liquid to the steps of the bottom of the wells, repeating the shape of the matrix, the removal of sludge along the grooves and radial grooves, the treatment of the well wall. A special technology for the manufacture of diamond drill heads with a complex geometry of the matrix has been devised. The performance of diamond drill heads of various designs was tested under the industrial conditions of drilling wells for water and at polymetal deposits. It has been established that in terms of the quality of the tasks to be solved and technical and economic indicators, they have a significant advantage in comparison with standard equipment in terms of the mechanical speed of drilling wells, energy costs, and structural integrity of the core. The comparative states of the shape, the transverse size of the hydrogeological well, the purity of the treatment of the wall of the latter, drilled by diamond drill heads and standard equipment with ball bits, are indicative. The structural integrity of the core selected by the regular column set HQ in an assembly with drill heads with a hydrojet effect of rock destruction is ensured